The Role of Islamic Education Teachers in Shaping Students’ Islamic-Based Character at SDN 2 Montong Beter - Sri Mawaddatul Aini; Mukammal; Sumiatun (Journal of Islamic Religious Studies, 2025)
Islamic-based character formation in elementary school students is a crucial aspect of education, aiming to ensure that learners not only acquire academic knowledge but also internalize moral, spiritual, and ethical values as guiding principles in daily life. Islamic Education (PAI) teachers hold a strategic role in instilling these values from an early age. This study seeks to address two main questions: (1) How do PAI teachers contribute to the formation of Islamic-based character in students? and (2) What supporting and inhibiting factors influence this process? Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation, involving the school principal, PAI teachers, and students as participants. Data analysis followed the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that: (1) the role of PAI teachers in shaping Islamic character is implemented through early instillation of adab, the integration of lectures with direct practice, the habituation of prayer before and after learning, and the provision of exemplary daily behavior; (2) Supporting factors include strong principal support and effective collaboration among teachers, while inhibiting factors involve limited parental engagement and restricted instructional time for PAI. Overall, the role of PAI teachers at SDN 2 Montong Beter proves effective in fostering Islamic character, though stronger collaboration between school and family is recommended to reinforce outcomes.